Analysis of Economic Indicators of Complex Production Processes - A.M, Korneev; L.S, Abdullakh (International Journal of Engineering and Technology, 2018)
The article describes the methodology for describing the economic indicators of management effectiveness and decision-making under conditions of complex multi-stage productions. The algorithm and the forecast model of the need for production resources are presented, that allow providing more complete information on costs and help in pricing for various products, significantly reducing the response time to economic and technological situation changes. Characteristics of technology parameters are linked to a multi-stage production process. As the semi-finished product passes through the processing stages, the values of the technological factors are fixed. Methods for estimating the influence of parameters of complex spatially-distributed systems on costs are presented. Important elements of costs that affect the product value are determined. Detailing the cost elements for the technological operations under study is carried out, the boundaries, where the largest amount of resources is spent, are determined.Â